KEBIJAKAN LUAR NEGERI PAKISTAN MENOLAK BERGABUNG KE KOALISI MILITER ARAB SAUDI DALAM MENGHADAPI KONFLIK YAMAN - Habib Budiman; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Conflict in Yemen has given impact to the region. Saudi Arabia as a country which directly border with Yemen has concerns with expanding of The Shia Houthis movement. By means of the Yemen President request, Saudi Arabia gathering power from its allies and lead a military coalition to rescue the Yemeni Government. And Pakistan is a country that has a very close relationship with Saudi Arabia asked to join with coalition. This research is aimed to explain the foreign policy of Pakistan in Yemen conflict, particularly to respond Saudi Arabia’s appeal to join the in military coalition to fight againts the Houthi group.This research theoretically has built by using Morghenthau Neoclassical Realism perspective on International Relationsand supported by Foreign Policy theory from James N. Rossenau. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods.This research also using nation-state as the level of analyze, the focus on this research is explain the causes of Pakistan foreign policy rejection to join in Saudi Arabia military coalition.Reseacrher has formulated answer-hypothesis which revealed the fact that instability of internal security is causes Pakistan refused Saudi Arabia request. Conflict between government and militant groups and fears of Pakistan government with conflict between Sunni-Shia would be worse considering that the sizeable of Shia's influence in Pakistan territory. This research has added one more explanation about the role of Iran as the biggest Shia country in cases development shia in Pakistan.Keywords :Yemen conflict, Military Coalition, Pakistan, Saudi Arabia, foreign policy, instability